A qualitative evaluation of remote training to develop a fitness surveillance system. (February 2023) - Egan, Cate A; Merica, Christopher B; Paul, David R; Bond, Laura; Rose, Seth; Martin, Andrew; Vella, Chantal
Objectives: In the USA, 18% of school-aged young people are classified as obese, and rural populations appear to be particularly at risk. Achieving high levels of fitness reduces the risk of obesity and underlying health conditions. To better understand youth obesity trends and fitness levels, annual fitness testing ([FT], that is, surveillance) in schools has been recommended. Although many K–12 schools conduct FT, surveillance programmes that compile unified standardised test results are rare. Design: Qualitative design. Setting: Physical education teachers from 11 schools ( n  = 13; n  = 4 men) participated in remote training about conducting FitnessGram FT. Methods: Data included two semi-structured interviews per teacher on experiences with distance fitness training, implementing FitnessGram, and data entry for annual surveillance. Results: Inductive analysis using axial and open coding identified four themes: (1) barriers prior to study, (2) study training, (3) implementation challenges and suggestions and (4) teacher feedback. Teachers had an interest in FT but lacked the recommended training and equipment needed to implement it annually. Conclusion: Teachers believed the training they received (as part of this study) prepared them to collect reliable and valid data, and that FT had benefits for their students and programmes. Every teacher expressed interest in reporting annual surveillance data. Efforts to train teachers for FT through virtual professional development may be a viable means of establishing a unified surveillance system.